The price of youth: commodification of young people through malleable risk practices. (13th September 2016) - Turnbull, Gavin
ABSTRACT: Risk has become a dominant part of theory and practice in young people's services over the past 30 years [Kemshall, H. 2008. "Risk, Rights and Justice: Understanding and Responding to Youth Risk." Youth Justice 8 (1): 21–37; Goldson, G. 2000. "Children in Need' or 'Young Offenders'? Hardening ideology, organizational change and new challenges for social work with children in trouble." Child and Family Social Work 5 (3): 255–265]. Young people are simultaneously described as 'at-risk' and risky, 'permanent suspects' [Mcara, L., and S. Mcvie. 2005. "The usual suspects? Street-life, young people and the police." Criminal Justice 5 (1): 5–36] with the potential for committing crime, using drugs, being sexually promiscuous or under-performing in the socio-economic climate [Turnbull, G., and J. Spence. 2011. "What's at risk? The proliferation of risk across child and youth policy in England." Journal of Youth Studies 14 (8): 939–959]. This paper reports on a UK study of youth practitioners' perceptions of young people in relation to 'risk' and how this affects practice. Findings identify a context where practitioners engage with notions of young people as at-risk or risky, managing tensions between external constructions and the 'real' individual on an on-going basis. 'Risk' becomes malleable, with young people's risk biographies being amplified or attenuated on the basis of the practitioner's view of needs, resource allocations, contracts, targets, practitioner or organisational fears, risk management processes, and the desire to get the best for the young person. Whilst of short-term benefit, this commodification of young people is counter-productive, magnifying the construction of youth as risky others. The paper calls for new approaches to challenge the continued dominance of the youth risk paradigm in practice, policy and the academic youth studies field.